The Skewed Voices and Lost Meaning: The Reflections of Multilingual Issues in the Cross-cultural Context - Ming-yeh Lee (Adult Education Research Conference, 2001)
The purpose of this paper is to discuss the correlative effects of multilingualism, as it is associated within a cross-cultural context. Strategies that were used to assure language accuracy and reliability of the study will also be discussed.